EFFECT OF HUMIC ACIDS AND SPRAYING WITH AMINO ACIDS AND ALCOHOLIC SUGARS ON THE CONCENTRATION OF SOME NUTRIENTS IN POTATO TUBERS AND THEIR AVAILABILITY IN THE SOIL - Said , Ezzeddin; Abdulrassoul, Kahtan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A field experiment was carried out at field of College Agricultural Engineering Sciences - University of Baghdad, during spring season 2022 to study the effect of adding humic acids to the soil and foliar applied amino acids and  alcoholic sugars on the concentration of some nutrients in potato tubers and their availability in the soil. The experiment was faetorial with split-split plot arrangement within randomized complete block desigen with three replicates the experiment included three factors, The first was the addition of humic acids to the soil at three levels(0, 20, 40) Kg ha-1 Asymbol of it (H0,H1,H2),  And the second factor foliar applied amino acids (0,250,500) mg L-1 A symbol of it (A1,A2,A3), the third factor foliar alcoholic sugars with concentrations (0, 20, 40) g L-1 A symbol of it(S1,S2,S3). The number of treatment was 27, The results indicated Single factors For level 40 Kg humic acid ha-1, 500 mg L-1 amino acid, 40 g L-1 alcoholic sugars gave a significant increase availability of N,P,K,Fe,Mn in soil and concentration of N,P and K in tubers. The bilateral interactions between treatments highest levels gave a significant increases in availability of N,P,K,Fe and Mn in soil and concentration of N, P and K in tubers. The triple interaction at concentrations (40 kg ha-1, 500 mg L-1, and 40 g L-1) gave the best results for all studied traies.